Interaction Between Investment, Exports, Human Development Index, Technology, and Corruption on Economic Growth of ASEAN Countries - Reza, Deft Syatir Putri; Soelistyo, Aris; Firmansyah, Muhammad (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2025)
This study aims to analyse the impact of foreign direct investment, exports, the human development index, technology, and corruption on economic growth in ASEAN. This quantitative analysis employs panel data regression to identify the variables affecting economic growth in ASEAN. This study encompasses ten ASEAN countries: Brunei Darussalam, Indonesia, Cambodia, Malaysia, Singapore, Thailand, Vietnam, the Philippines, Myanmar, and Laos, covering the period from 2010 to 2023. This study's results demonstrate that foreign direct investment, exports, the human development index, and technology significantly and positively influence economic growth in ASEAN. Corruption does not significantly impede economic growth within ASEAN. The variables of foreign direct investment, exports, the human development index, technology, and corruption collectively exert a significant influence on economic growth in ASEAN. This study introduces technology as a significant influencing variable. The ASEAN government persists in upholding stability and enhancing the national economy. The government must implement decisive measures in state security and enhance transparency to prevent an increase in state corruption. Further research should focus on broadening the variables associated with economic growth and employing diverse methodologies.